EVALUATION OF THE OCCLUSAL COMPOSITE RESIN RESTORATIONS BASED ON CARS CRITERIA AND OPTICAL METHODS: A CROSS-SECTIONAL STUDY - R. Brânzan; Angela Ghiorghe; Claudiu Topoliceanu; Andrei Georgescu; N. Tofan; Sorin Andrian (Romanian Journal of Oral Rehabilitation)
Aims of the study were as follows: to assess the status of posterior coronal composite resin restorations using the CARS criteria and the optical methods DIAGNOdent Pen and VistaCam; to analyze the correlation between clinical CARS scores and the scores recorded by the DIAGNOdent Pen (KaVO) and VistaCam (Dürr Dental) devices in the evaluation of composite resin restorations. Materials and methods: The retrospective study included 32 patients (mean age: 24.25 ± 2.918 years; gender: 13 males, 19 females; p = 0.526). A total of 161 direct composite resin restorations aged between 3 and 5 years were evaluated clinically and using DIAGNOdent Pen (KaVo) and the VistaCam device (Dürr Dental). Statistical analysis was conducted using SPSS 29.0, applying both parametric and non-parametric tests to evaluate associations between clinical findings and optical methods outcomes. Results: Based on CARS scores, 54% of restorations showed enamel-limited demineralization, with no cases of extensive cavitation. DIAGNOdent Pen results indicated that 49.7% of restorations had signs of enamel or dentin demineralization, with a mean value of 18.40 ± 15.50. VistaCam evaluation revealed that 30.4% of restorations had varying degrees of demineralization, while 69.6% presented healthy enamel margins, with a mean value of 0.73 ± 0.88. Conclusions: More than half of the restorations exhibited various degree of enamel demineralization. The overall consistency among CARS scores, DIAGNOdent Pen readings, and VISTACam values supports the integration of fluorescence-based technologies into routine clinical practice for improved diagnostic accuracy and conservative treatment planning.